Europeanizing the labour market: Employee mobility and company recruiting methods - Ulrich Walwei; Heinz Werner (Intereconomics, 1993)
With the completion of the single European market steps are to be made towards eliminating remaining impediments to the free movement of labour between Community countries such as an inadequate flow of information or the non-recognition of educational or training qualifications. How do companies respond to the extension of national labour markets by a European component?
Keywords: 330; European Community